Using a surface response method for experimental design to optimize the analysis of taurine in food supplements by capillary electrophoresis - Huy, Nguyen Manh; Dam, Nguyen Thanh; Anh, Duong Hong; Viet, Pham Hung (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4DO - 10.25073/2588-1140/vnunst.4657, 2017)
Abstract: This study focus on using surface response method to optimize the taurine analysis by capillary electrophoresis with contactless conductivity detector. A response surface method (RSM) coupled with a central composite model (CCD) comprising 30 experiments was developed with 4 factors including concentration of Tris buffer, pH value, separating potential and sample injection time. The best set of factor levels for taurine analysis was found as follows: 150 mmol/L of Tris concentration, pH = 8.96, separation voltage of -10 kV, the sample injection time of 60 seconds. The validation of analytical method showed the detection limit for taurine was 0.266mg/L, linearity range from 1 to 500 mg/L, relative standard deviation values ​​for peak areas and migration times were less than 3.16%, the linear correlation coefficient gained 0.999. Recovery efficiency of taurine in several food supplement matrixes such as: fresh milk, milk powder, energy drink were in range from 91.9% to 101.7%.